2019
DOI: 10.1029/2019gl083519
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Initial Condition for Skillful Surface Prediction in the ECMWF Model

Abstract: The subseasonal‐to‐seasonal prediction of boreal‐winter sea‐level pressure (SLP) is investigated by examining 19‐year reforecast data sets from the European Centre for Medium‐Range Weather Forecasts ensemble prediction system. Based on a pattern anomaly correlation coefficient of 0.6, the model reliably predicted the extratropical SLP anomalies with a maximum forecast lead time of 9.8 days. This prediction skill, however, varies significantly from one forecast to another. The forecasts with relatively high ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…A higher prediction skill in the stratosphere is also associated with a higher prediction skill in the troposphere (DJF in the NH and OND in the SH). This is consistent with Choi and Son () who showed that the tropospheric prediction skill is sensitive to stratospheric initial conditions. Sigmond et al () and Tripathi et al () also showed that surface prediction skill is extended when models are initialized during weak or strong polar vortex state in comparison to normal condition.…”
Section: Resultssupporting
confidence: 92%
“…A higher prediction skill in the stratosphere is also associated with a higher prediction skill in the troposphere (DJF in the NH and OND in the SH). This is consistent with Choi and Son () who showed that the tropospheric prediction skill is sensitive to stratospheric initial conditions. Sigmond et al () and Tripathi et al () also showed that surface prediction skill is extended when models are initialized during weak or strong polar vortex state in comparison to normal condition.…”
Section: Resultssupporting
confidence: 92%
“…Examples where initial atmospheric conditions can provide predictability beyond the usually assumed limit have been demonstrated, not only for the extratropics but also for the tropics, and we now know that in some situations, for example when sudden stratospheric warmings occur, the initial conditions in the stratosphere can have more impact than initial conditions in the ocean Polvani et al, 2017). This suggests that initial atmospheric conditions in the stratosphere are likely to be more important for long-range forecasts than previously assumed (Mukougawa et al, 2005(Mukougawa et al, , 2009Stockdale et al, 2015;Noguchi et al, 2016Noguchi et al, , 2020aChoi and Son, 2019;O'Reilly et al, 2019;Nie et al, 2019), not least because the overturning and breaking of Rossby waves in the stratosphere is followed by long-lived atmospheric anomalies due to synoptic-scale eddy feedbacks that prolong the effects in the troposphere (Kunz and Greatbatch, 2013;Kang et al, 2011a;White et al, 2020). More research on the initial conditions in the stratosphere might therefore help to reveal potential for further improvements in prediction skill.…”
Section: Discussionmentioning
confidence: 91%
“…Examples where initial atmospheric conditions can provide predictability beyond the usually assumed limit have been demonstrated, particularly for the extratropics but also for the tropics, and we now know that in some situations initial conditions in the ocean have less impact than initial conditions in the stratosphere . This suggests that initial atmospheric conditions are likely to be more important for long range forecasts than previously assumed (Mukougawa et al, 2005(Mukougawa et al, , 2009Stockdale et al, 2015;Noguchi et al, 2016Noguchi et al, , 2020aChoi and Son 2019;O'Reilly et al, 2019;Nie et al, 2019), not least because the overturning and breaking of Rossby waves in the stratosphere is followed by long lived atmospheric anomalies due to synoptic scale eddy feedbacks that prolong the effects in the troposphere (Kunz and Greatbatch 2013) and enhance long range predictability .…”
Section: Discussionmentioning
confidence: 93%